Límites a la política fiscal y monetaria en economías peque\~nas y abiertas - Ariel Dvoskin; Matias Torchinsky Landau (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2023)
– In this paper we examine how the balance-of-payments constraint can limit output and income distribution in a small economy open to both commercial and financial flows, as well as constrain fiscal and monetary policies. We do so by extending a Sraffian supermultiplier growth model to consider current and capital accounts and endogenous money. Expansive fiscal policy boosts output and its long run growth rate, but also has a negative impact on the balance-of-payments by increasing the demand for imports. Based on these results, we derive the value of government spending that maximises output maintaining external equilibrium. Monetary policy can also play a significant role in the external sector, since high domestic interest rates can attract foreign financial flows. It does so in a non-monotonic way, since, by providing foreign currency, these flows can finance the external deficit resulting from a high output level, but they can also lead to a higher interest burden on the balance-of-payments. This trade off allows us to find the level of the interest rate that maximises external space. This also implies that raising interest rates might allow for better real wages. Finally, we compare the case of domestic and foreign denominated debt, finding that the former is less contractionary and allows for a faster recovery of reserves, but does not lead to higher growth rates.
Keywords: 330; Thirlwall's law; Sraffian supermultiplier; fiscal policy; monetary policy; income distribution; structuralism; endogenous money